REPLIKASI DATA MENGGUNAKAN DETECTION CONTROLLER MODULE UNTUK MENCEGAH CONGESTION DI DATA CENTER - Erna Auparay; Royyana Muslim Ijtihadie (Department of Informatics, Institut Teknologi Sepuluh Nopember, 2018)
Replication of data in a distributed manner is one of the important phases in the process of centralized data distribution. Replication of data does a copy or duplication technique in the process of data distribution logic. This distribution will be interconnected either system or applicative data is distributed in the network computer. Distributed storage media from one storage medium to another storage medium will implement the synchronization between the source server to the destination server so that the data consistency can be guaranteed. The use of controller-controller Software Defined Network (SDN) in the data center that is to control the process distribution data to multiple locations storing the same data. This is very useful in these locations require the same data or require a separate server in the manufacture of reporting applications. SDN controller-controller is also used to control the distribution entities, which may exhibit different behavior on event triggers, but in the case of traffic flow density distribution in the data center network that causes congestion/bottlenecks until need their completion strategies. Therefore, this paper will discuss what approach to data replication strategies used to cope with the density of the network traffic flow.